2012
DOI: 10.1111/hae.12005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety during formulation switch of a pasteurized VWF/FVIII concentrate: results from an Italian prospective observational study in patients with von Willebrand disease

Abstract: Summary. Von Willebrand disease (VWD) is an inherited bleeding disorder caused by the quantitative or qualitative deficiency of von Willebrand factor (VWF). Replacement therapy with plasma-derived VWF/factor VIII (FVIII) concentrates is required in patients unresponsive to desmopressin. To assess the efficacy, safety and ease of use of a new, volume-reduced (VR) formulation of VWF/FVIII concentrate Haemate ® P in patients requiring treatment for bleeding or prophylaxis for recurrent bleeding or for invasive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 25 publications
(63 reference statements)
0
31
0
1
Order By: Relevance
“…Eighteen studies used concentrate to control bleeding , but one was excluded due to lack of detail. The 17 remaining studies covered 614 patients undergoing 914 surgical procedures (where reported 178 interventions were classified as major and 257 as minor surgery) (see Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen studies used concentrate to control bleeding , but one was excluded due to lack of detail. The 17 remaining studies covered 614 patients undergoing 914 surgical procedures (where reported 178 interventions were classified as major and 257 as minor surgery) (see Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Two guidelines give recommended dose of concentrate to cover major surgery in terms of dose of FVIII:C. However, a crucial consideration is that different preparations of factor concentrate have different ratios of FVIII:C to VWF:RCo. The manufacturers quote values from 2.4:1 (Haemate) to 0.75:1 (Immunate) in their SMPCs (Table ), but not all countries label VWF/FVIII concentrates with their VWF:RCo content, so in these cases, FVIII content must be used to guide replacement therapy and this may lead to less than optimal dosing of VWF:RCo.…”
Section: Discussionmentioning
confidence: 99%
“…All the products except the recombinant VWF lack to a variable degree high molecular weight VWF multimers and also differ regarding the ratio of VWF:RCo to FVIII:C and the virucidal methods employed (Table ). Their use in the setting of major surgery has been evaluated by a number of prospective studies .…”
Section: Replacement Products For Von Willebrand Diseasementioning
confidence: 99%
“…Cela entraîne un faible nombre de références concernant ce sujet précis [4][5][6][7][8][9]. En revanche, au cours de ces dernières années, de nombreux articles ont été publiés en utilisant un protocole semblable mais en utilisant un concentré VWF/FVIII comme traitement substitutif pour les patients atteints de maladie de Willebrand [10][11][12][13][14]. L'utilisation de ce traitement permet une meilleure prévention hémorragique des patients, notamment ceux résistants à la desmopressine.…”
Section: éVolution Des Pratiquesunclassified